Biochar amended mine tailings: observations on plant survival - Fellet G; Zerbi G.; MARCHIOL, Luca (2011)
Biochar (BC) is a C rich product obtained by thermal decomposition of organic material, such as wood or manure, under limited supply of oxygen (O2), at relatively low temperatures (<700 °C). It is a black material composed of stable C that have been proposed as an alternative solution for C sequestration. The effects that BC can produce on both the chemical and physical properties of soil have been described by many authors. Its application on polluted soils or matrices may have significative variations on the migration and bioavailability of the pollutants, therefore on the phytotoxicity that hinders plant growth. Four types of feedstocks were pyrolized using the LuciaStove (WorldStove), a top-lit pyrolytic gasifier cook-stove, and the BCs obtained after the process were mixed in three doses (0, 0.75 and 1.5%dw/dw) with metal-rich mine tailings (23.6±0.656 mg kgss-1 Cd; 3,218±185 mg kgss-1 Pb; 118±9.32 mg kgss-1 Tl; 13,672±336 mg kgss-1 Zn) from the mining site of Cave del Predil (NE, Italy). A pot experiment will be set up with three species (Anthyllis vulneraria, Poa alpina, Biscutella laevigata) from the mining site. The plants will be grown for 45 d on the four substrates. At the end of the growing period, plants will be harvested and analyzed to measure the elemental composition, the metal bio-accumulation and the biomass production. The substrates will be characterized in terms of chemical and physical properties, particularly focusing on heavy metals and metalloids composition, mobility of the pollutants, but also fertility and phytotoxicity. The fertility of the mine tailings, in terms of nutrient and water retention, is expected to be increased by the treatments while the phytotoxicity, in terms of bioavailability and leachability of pollutants, is expected to be lowered. These changes are expected to be reflected on the plant growths.